Cognitive Function Impairment in Patients with Multiple Sclerosis - Lučev, Emil (Array, 2007)
Impairment of cognitive functions in patients diagnosed with multiple sclerosis, as well as the development of neurological and psychiatric symptoms depends on a number of factors such as localization of lesion in the central nervous system, interaction between demyelinized areas, premorbid status of the CNS, time of development and pace of illness, point of introduction of specific and non-specific pharmacotherapy as well as physical therapy and psychological support. Cognitive function impairment can, however, influence further development of the disease as it can lead to irregular use of pharmacotherapy, refusal of physical therapy, reduction or discontinuation of social contacts inside or outside the family circle, and non-cooperation with the psychotherapist. In the present study, cognitive functions in multiple sclerosis patients were evaluated by the Clinical Dementia Rating (CDR) scale, which includes assessment of memory, orientation, judgment and problem solving, community activities, home and hobbies and personal care. The study included 23 patients with relapsing and remitting multiple sclerosis, 12 female and 11 male. All participants had at least two relapses in the four years prior to testing. Their age ranged from 28 to 53, with median of 40 years. The duration of the disease varied from 3 to 8, with median of 6 years.EDSS scores were in range from 0.0 to 3.0, while MMSE results ranged from 26 to 30, with median of 28. Nine patients had elementary education, 12 patients were high school graduates and 2 were university graduates. The testing was conducted in period from January 1 2004 to December 31 2006 on workdays, between 13 h and 16 h. The subjects and, when necessary their caretakers were guaranteed anonymity and were informed that the data collected would be used strictly for the purpose of scientific research. Results acquired with CDR indicated that seven patients met the criteria for mild dementia (F4, M1), two for moderate dementia (F1, M1)and two for severe dementia (F1, M1), so that total 47.8% of the patients were diagnosed with dementia. These results correspond to previous studies on US and English samples. All multiple sclerosis patients with a positive CDR result also met the DSM-IV criteria for dementia. A timely diagnosis of dementia development in multiple sclerosis patients is important as it allows well-timed pharmaceutical and AchE inhibitor therapy as well as psychotherapy. Generally administered psychotherapy is supportive therapy, while patients in early stages of dementia can be treated with person-centered Carl Rogers phenomenological therapy.